Low-cost photogrammetry for culture heritage - Shults, Roman; Krelshtein, Petro; Kravchenko, Iulia; Rogoza, Olga; Kyselov, Oleksandr (International Conference “Environmental Engineering”, 2017)
Culture heritage will always remain one of the priorities of any state. Taking a cultural or historical object under protection is impossible without inventory. The best technology, which allows getting high-quality inventory, is close-range photogrammetry. Unfortunately, the full capabilities of this technology is fully owned by professionals only. The situation changed significantly with the advent of mobile devices that are equipped with digital cameras and low-cost software that does not require any special knowledge in the theory and practice of photogrammetry. These developments have been called low-cost photogrammetry technologies. In the present study, we examined the use of smartphones and nano UAV and PhotoScan software for solve the problem fortifications II World War inventory near the city of Kiev. For qualitative data, the calibration of digital cameras in smartphones and ultra-light UAV was performed on calibration bench. One of the features of this project was the integration of the terrestrial photos and photos captured by nano UAVs. As a result of work performed were obtained 3D models of fortifications. Results showed high efficiency of the low-cost photogrammetry technologies. At the end of work some practical guidelines were provided, how to get high-quality data using low-cost photogrammetry technologies.